EFFECT OF EXTRACURRICULAR ACTIVITIES, INTRACURRICULAR ACTIVITIES AND CULTURE OF PESANTREN ON ENHANCEMENT OF STUDENTS LEARNING ACHIEVEMENT IN PP. BAITUL ARQOM JEMBER - Noga Riza Faisol; Gatot Sugeng Purwono; Agustin HP (MBA - Journal of Management and Business Aplication, 2019)
Pesantren (Islamic Boarding School) is one of the oldest educational systems in the archipelago (Indonesia). Classical method of a Kiai (religious leader of Moslem) as a figure and the mosque as a center of education proved to contribute knowledge and education character of the nation's children. Before modern education gives its influence, the classic, written or unwritten rules become a culture of positive direction for the santri (students of Islamic Boarding School) in it. Countless warriors and heroes in their era gave a share in the journey of this nation. Pesantren Modern is one of the evolutions of pesantren in responding to the development of the time. The principle of "Al mukhafadatualaalqodimiassholeh, walakhdualjadidi al aslah" or means keeping the good old tradition and take something new and better is a foothold in the management of the boarding school. The development is adjusted with the syllabus of the education curriculum in accordance of the level of elaborating the compulsory activities or called as Intracurricular activities as well as selected activities or Extracurricular. Another important role is the culture in surrounding pesantren as a container or synergy activities in everyday life. This article is more practical try to review the relationship of variables between the influence of extracurricular activities, intracurricular activities and pesantren culture on improving student achievement in PP. Baitul Arqom Jember. This study was used a quantitative approach by collecting primary and secondary data with various methods of data analysis and validity test to determine the level of validity and reliability.